THE ROLE OF THE INNATE IMMUNE SYSTEM IN THE IMMUNOPATHOGENESIS OF CHRONIC OBSTRUCTIVE BRONCHIAL DISEASE - Nabieva U.P.; Khamidullaeva N. А.; Tairova S. F. (Scholars Digest Publishing, 2024)
Chronic obstructive pulmonary disease (COPD) is a common, socially significant disease characterized by progressive restriction of airflow as a result of chronic bronchial inflammation. Although the causes of COPD are considered known, the pathogenesis of the disease continues to be an urgent topic for study. The mechanisms of the innate immune system are involved in various links in the pathogenesis of COPD, lead to the preservation of chronic inflammation in the bronchi, their bacterial colonization and disruption of the structure and function of the lungs. Bronchial epithelial cells, neutrophils, macrophages and other cells are involved in the development and progression of the disease through multiple compromised immune mechanisms.
Keywords: COPD, innate immune system, inflammation, bronchial epithelium.